Biomedical Material for Stent Application: Current Status and Future Challenges - Sukmana, Irza; Chyanegoro, Arifo Gunawan; Sugiri, Agus (INSTEP Network, 2021)
Cardiovascular disease is the leading cause of death worldwide. Arterial stenting as a transluminal angioplasty procedure allows re-opening of narrowed vessels and restoring normal blood flow with stent placement. The development of stents ed at the end of 19 century with bare-metal stents (BMS). Now, it has been based on the application of biodegradable or natural decomposed and coated stents. The coated stent has been found to improve BMS properties in terms of biocompatibility, cytotoxicity, and better mechanical and biophysical properties. Also, a biodegradable stent may support the blood micro-vessel during the estimated period of time before downgraded constituents. The biodegradable stent also allows a reinsertion for several months to improve the vessel wall's quality. This paper describes the possible materials for stents and their properties such as design criteria, degradation behavior, disadvantages, and advantages with clinical and preclinical trials to date. Stent degradation allows reinsertion of the stent after several months and improves the vessel wall quality. This paper focuses on developing materials for stents, which describe the possible materials for stents and their properties. Furthermore, the current clinical trial of the new proposed stent will also be highlighted.